Ensiling natural meadow forage in «Tierra del Fuego», Argentina - Jaurena, G.; Livraghi, E.; Álvarez Ugarte, D.; Ceccaldi, E.; Molina, R. (Spanish Journal of Agricultural Research, 2010)
Livestock activity in the Argentinian «Tierra del Fuego» island is based on highly variable natural grasslands (NG). The conservation of fodder, despite the unfavorable environment, is restricted to hay; conservation as silage could be constrained by fodder quality and low temperatures. The objective was to assess the quality of NG silages fermented under contrasting storing conditions. Typical meadow forage was ensiled in minisilos and stored under shelter (Shelter) or in the field (Field) in a complete block design with repeated measures in time (t). Forage was chopped and inoculated with lactic acid bacteria plus enzymes, and harvested with 420 g dry matter (DM) kg–1 fresh matter, 111 g crude protein kg–1 DM, 665 g ash-free neutral detergent fibre kg–1 DM, and 64 g water soluble carbohydrates kg–1 DM. Shelter minisilos had higher metabolizable energy concentration at 236 d (PTrat×t = 0.03; Shelter = 10.2 ; Field = 9.6 MJ kg–1 DM, P = 0.01), and lower DM losses (Shelter = –0.2; Campo = 22%, P = 0.02) and values of pH and N-NH3/total N (Field: 5.6 and 12% and Shelter: 4.4 and 6.8%, P = 0.01). Fermentation acids concentration was similar for both treatments with preponderance of lactic acid, but acetic acid concentration increased over time (Pt = 0.01). It was concluded that in «Tierra del Fuego», natural meadow forage quality is compatible with ensiling, but environmental conditions can limit the fermentation process.